Enhancing tuber yield and nutraceutical quality of potato by supplementing sunlight with LED red-blue light - Pannico, Antonio; Arouna, Nafiou; Fusco, Giovanna Marta; Santoro, Piero; Caporale, Antonio Giandonato; Nicastro, Rosalinda; Pagliaro, Letizia; De Pascale, Stefania; Paradiso, Roberta (Frontiers in Plant Science, 2025)
IntroductionWe investigated the influence of genetic material and light spectrum on plant performance of two cultivars of potato (Solanum tuberosum L.), ‘Colomba’ and ‘Libra’, grown in greenhouse, in the view of future plant cultivation in Space and terrestrial vertical farming and controlled environment agriculture under limiting light conditions.MethodsThe effects of 100% natural light (CNT) and two lighting treatments, in which 30% of solar radiation was replaced by red and blue LED light, RB 1:1 and RB 2:1, were evaluated on plant growth, gas exchange, and tuber yield and quality.ResultsIn CNT plants, net photosynthesis (NP) was similar in the cultivars, while the aerial biomass and tuber yield were greater in ‘Libra’. In ‘Colomba’, NP and plant leaf area were unaffected by lighting treatments, however tuber yield increased under RB 2:1. Conversely, in ‘Libra’ both the aerial biomass and tuber production decreased in RB 2:1. Tubers of ‘Colomba’ contained higher concentrations of most minerals than ‘Libra’, probably due to different genetic traits and the slightly lower biomass (concentration effect). Red-blue lighting did not alter the mineral content of tubers. ‘Colomba’ prioritized the accumulation of free amino acids, GABA, and polyphenols, enhancing the plant stress response and antioxidant capacity, and adapted well to variable light conditions, with significant increases in tuber yield under LED treatments. Differently, ‘Libra’ focused on synthesis of carbohydrates, and essential amino acid content was lower compared to ‘Colomba’.DiscussionOur findings underline the importance of genotype selection and highlights how light spectrum can improve the plant performance in potato. This knowledge could be useful in controlled environment agriculture and indoor cultivation (i.e., vertical farming) as well as in space research on potato, as this crop is a candidate for plant-based regenerative systems for long-term missions.